2001
DOI: 10.1359/jbmr.2001.16.4.731
|View full text |Cite
|
Sign up to set email alerts
|

Mild Heat Shock Induces Proliferation, Alkaline Phosphatase Activity, and Mineralization in Human Bone Marrow Stromal Cells and Mg-63 Cells In Vitro

Abstract: Bone formation has been shown to be stimulated by local diathermy in vivo; however, the mechanisms involved in this heat-induced osteogenesis are unclear. In this study, we investigated the direct effect of temperature on human bone marrow-derived stromal cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 42 publications
(62 reference statements)
9
117
1
Order By: Relevance
“…This observed regenerative response is in agreement with previous studies that showed that exposure of osteoprogenitor cells to mild heat-shock (39-42.58C)-induced differentiation along the osteoblastic line and enhanced mineralized nodule formation [15,24]. In these studies, however, the duration of exposure to elevated temperatures is much longer than what is likely to occur during surgical cutting procedures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observed regenerative response is in agreement with previous studies that showed that exposure of osteoprogenitor cells to mild heat-shock (39-42.58C)-induced differentiation along the osteoblastic line and enhanced mineralized nodule formation [15,24]. In these studies, however, the duration of exposure to elevated temperatures is much longer than what is likely to occur during surgical cutting procedures.…”
Section: Discussionsupporting
confidence: 92%
“…The mineralized matrix was quantified by alizarin red S staining methods [15,24]. Alizarin red S (1 mole) binds to two moles of calcium, forming an alizarin red S-calcium complex.…”
Section: Quantification Of Mineralizationmentioning
confidence: 99%
“…Nevertheless, some previous studies showed that HS induces a positive effect on bone growth and remodeling in vitro and in vivo. 13,33 Recently, conditions involving heating and growth factors in combination resulted in the inhibition of osteoclast differentiation and bone-resorptive processes in the bone microenvironment. 32 The close relationship between HSP synthesis and tissue regeneration under HS conditions has also been reported.…”
Section: Et Almentioning
confidence: 99%
“…12 Furthermore, MHS induces the proliferation and differentiation of human bone marrow stromal cells and MG-63 cells in vitro. 13 The conditioned culture media acquired from heat-treated osteoblasts enhances osteocalcin secretion and mineralization in bone marrow mesenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, mild heat shock has been shown to positively regulate cell survival and proliferation. For example, mild heat shock facilitates activation of resting lymphocytes for proliferation and effecter formation (17), stimulates bone marrow stromal cell proliferation (18), and induces the synthesis of cyclin D1, which plays a critical role(s) in the G1 progression of the cell cycle through multiple Ras signal pathways involving Rac1/NADPH oxidase, ERK, and PI3K (19). Furthermore, mild heat shock-induced heat shock protein (HSP) expression is regulated by a small GTPase Rac1, while harsh heat shock-induced HSP expression is not (20).…”
Section: Introductionmentioning
confidence: 99%